Case report: Severe hypertension-induced priapism in an infant with unrecognized autosomal recessive polycystic kidney disease - Konopásek, Patrik; Ptáčníková, Natálie; Toni, Ledjona; Zieg, Jakub (Frontiers in Pediatrics, 2023)
Priapism is a urologic emergency requiring prompt management. There are three types of priapism: stuttering (intermittent), non-ischemic (high-flow/arterial), and ischemic (low-flow/veno-occlusive). Here, we present the first case of an infant with recurrent non-ischemic priapism as the first sign of severe hypertension. An 11-month-old infant was admitted to the hospital for high-flow priapism. On admission, he was found to have severe hypertension that required a combination of five antihypertensive drugs; abdominal ultrasound showed polycystic kidneys, splenomegaly, and a parenchymal liver lesion. The priapism resolved spontaneously and did not recur again after the initiation of antihypertensive treatment. Genetic analysis confirmed autosomal recessive polycystic kidney disease (ARPKD). We found no other explanation for the priapism, such as genital trauma, hematologic disease, or anything else. Decreased nitric oxide (NO) bioavailability seen in patients with hypertension seems to be the principal mechanism of hypertension causing priapism. This hypothesis is supported by animal models of genetically modified mice lacking nitric oxide synthase. The same mechanism is thought to be the genesis of priapism and other complications, such as pulmonary hypertension, in patients with sickle cell disease. We present a case of severe hypertension-associated priapism in a child with unrecognized ARPKD. The endothelial dysfunction with decreased NO bioavailability seen in patients with hypertension may be the principal pathogenic mechanism.